Evaluation of the Implementation of a Well-being Promotion Program for College Students - Long, Robyn; Kennedy, Megan; Malloy Spink, Katie; Lengua, Liliana J. (Frontiers in Psychiatry, 2021)
Stress that undergraduate students experience is a growing public health concern, and there is increasing attention to programs that promote protective factors and skills to support resilience and well-being. Be REAL (REsilient Attitudes and Living) is a program that has been shown to increase students' use of effective coping strategies, mindfulness, and sense of well-being. This study examined whether the program would be effective when delivered by university staff who mentor or advise students. Methods: Eleven university staff advising or mentoring students delivered Be REAL in a variety of campus settings to 271 students, and 116 students completed pre- and post-test assessments to evaluate potential changes in stress reduction, managing emotions, coping, social connections, well-being and mental health. Results: Students who participated in Be REAL showed significant pre to post-test improvements in perceived stress, emotion dysregulation, coping, social connection, self-compassion, and symptoms of anxiety. There was also a trend toward improvements in symptoms of depression. Conclusions: The findings suggest that training university staff who work with students to deliver well-being programs is a potential avenue for supporting college student mental health, and a more rigorous evaluation of the Be REAL program is warranted.